A macrolactonization approach to the total synthesis of the antimicrobial cyclic depsipeptide LI-F04a and diastereoisomeric analogues - Cochrane, James R.; Yoon, Dong Hee; McErlean, Christopher S. P.; Jolliffe, Katrina A. (Beilstein Journal of Organic Chemistry, 2012)
The cyclic peptide core of the antifungal and antibiotic cyclic depsipeptide LI-F04a was synthesised by using a modified Yamaguchi macrolactonization approach. Alternative methods of macrolactonization (e.g., Corey–Nicolaou) resulted in significant epimerization of the C-terminal amino acid during the cyclization reaction. The D-stereochemistry of the alanine residue in the naturally occurring cyclic peptide may be required for the antifungal activity of this natural product.
Keywords: antifungal; cyclic depsipeptide; epimerization; lipopeptide; macrolactonization; peptides